The diversifying strategy of market and tourism product as a mechanism to face the negative reflections of tourism sector analysis of international experiences - Bagdadi Bilal; Chekalil Imane (Journal of North African Economies, 2025)
This study aims to review the negative repercussions of the tourism sector's sensitivity and responsiveness to negative variables and how it is affected by economic, security and media fluctuations, as well as to find strategic marketing solutions to the problem of sensitivity and negative repercussions resulting from it. Our problem is how to avoid the negative repercussions of the tourism sector's sensitivity and economic fluctuations, then we will present international experiences that have been significantly affected by security or economic disturbance. Through our study, we found that tourism demand is determined by physical, psychological and behavioral factors, and control of tourism markets is through a competitive marketing mix that is formulated appropriately and flexibly.